An Hourglass truss lattice structure and its mechanical performances. (5th June 2016) - Feng, Li-Jia; Wu, Lin-Zhi; Yu, Guo-Cai
Abstract: This paper focuses on improving the strength of truss lattice sandwich structures by optimizing the topology structure. A new Hourglass truss lattice sandwich structure is then designed and fabricated by a snap-fit method. The out-of-plane and in-plane compressive properties of the Hourglass lattice sandwich structure are investigated theoretically and experimentally, and the measured results are compared with the analytical predictions. Results show that the low relative density Hourglass lattices have higher peak out-of-plane compressive strengths than the pyramidal lattices. Moreover, the peak in-plane compressive loads of Hourglass lattice sandwich structures are superior to the pyramidal sandwich structures. Therefore, the Hourglass lattice sandwich structure can be considered as a promising candidate in high specific strength lightweight structures. Graphical abstract: Highlights: Hourglass lattice sandwich structure is proposed and fabricated by a snap-fit method. Out-of-plane compressive strengths of the Hourglass lattices outperform the competing panels. In-plane compressive strengths of Hourglass sandwich panels are superior to pyramidal panels. A compressive model is proposed to predict the compressive strengths of sandwich structures.